Indeterminate Brooke-Rose. Issue 2 (7th February 2018) - Jordan, Julia
ABSTRACT: Christine Brooke-Rose is fascinated by the notion of indeterminacy, and throughout her career draws parallels between the science of uncertainty and the shifts in thinking engendered by quantum theory and the experimental literature of the 1960s and 1970s. Indeterminacy is an ambiguous term when applied to the literary text. If we call a text indeterminate we might mean that it has contradictory meanings or is open to multiple, equally weighted, possible interpretations, ones which the text itself does nothing to resolve. Here I offer a reading of Brooke-Rose's novel Such (1966) which argues that the novel is less indeterminate than it is about indeterminacy; that it does not so much present ambiguous or contradictory interpretive lines as offer a reflection on what the act of interpretation does, and what it might make happen; that it does not withhold knowledge from the reader so much as make the reader question the ways in which knowledge is itself implicated in the world around us. In the end, the novel offers us what amounts to an ethics of indeterminacy, suggesting that we should be wary of all acts of interpretation, and alert to their potential for malignity or invasiveness.